Is biportal technique/endoscopic spinal surgery satisfactory for lumbar spinal stenosis patients?: A prospective randomized comparative study - Kang, Taewook (Medicine (Baltimore), 2019)
BACKGROUND: Lumbar decompressive surgery is a standard surgical technique for lumbar spinal stenosis. Many new surgical techniques have been introduced, ranging from open surgery to minimally invasive procedures. Minimally invasive surgical techniques are preferred because patients experience less postoperative pain and shorter hospital stays. However, the success rate of minimally invasive techniques have been controversial. The object of this study was to assess the feasibility of spinal decompression using biportal technique/endoscopic surgery compared with microscopic surgery. METHODS: Seventy lumbar spinal stenosis patients undergoing laminectomy were included in this study. A number table was used to randomize the patients into two groups: a biportal technique/endoscopic surgery group (BG-36) and a microscopic surgery group (OG-34). One surgeon performed either biportal technique/endoscopic decompression or microscopic decompression using a tubular retractor, depending on the group to which the patient was randomized. Perioperative data and clinical outcomes at postoperative 6 months were collected and analyzed. RESULTS: The demographic data and level of surgery were comparable between the two groups. A shorter operation time (36 ± 11 vs 54 ± 9 min), less hemovac drain output (25.5 ± 15.8 vs 53.2 ± 32.1 ml), less opioid usage (2.3 ± 0.6 vs 6.5 ± 2.5 T) and shorter hospital stay (1.2 ± 0.3 vs 3.5 ± 0.8 days) were shown in BG. The BG experienced no significant differences in clinical outcomes compared with OG. Favorable clinical outcomes were shown at 6 months after surgery in both groups. CONCLUSION: Lumbar decompressive surgery using biportal technique/endoscopy showed favorable clinical outcomes, less pain and a shorter hospital stay compared to microscopic surgery in patients with lumbar spinal stenosis.